The Role of Land Deed Officials in Legal Protection of Land Grants Related to Agrarian Reform in Kalasey Dua - Felicia Gabriela Supit (International Journal Labs, 2026)
This study aims to examine the land grant policy issued by the Provincial Government of North Sulawesi to the Ministry of Tourism and Creative Economy through Governor's Decree No. 368 of 2021, from the perspective of agrarian reform. This study also analyzes the role of the Land Deed Official (PPAT) in providing legal protection during the land grant process in Kalasey Dua Village. The method used in this research is normative legal research with a descriptive-analytical approach. The study collects and analyzes primary, secondary, and tertiary legal materials related to the land grant policy, agrarian reform, and the role of PPAT. The findings show that the land grant policy is not in line with the agrarian reform principles mandated by the Basic Agrarian Law and other related regulations. The role of PPAT is crucial in ensuring that the land grant process complies with applicable laws and provides effective legal protection for the community. The conclusion of this study is that the land grant policy implemented by the Provincial Government of North Sulawesi contradicts the principles of agrarian justice, and PPAT plays a key role in ensuring legal compliance to prevent further agrarian conflicts in the community.